2010
DOI: 10.1038/aja.2010.40
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins in spermatozoa and testicular germ cells: identification and potential role

Abstract: Mammalian spermatozoa have relatively high water permeability and swell readily, as in the hypo-osmotic swelling test used in the andrology clinic. Physiologically, spermatozoa experience changes in the osmolality of the surrounding fluids in both the male and the female tracts on their journey from the testis to the ovum. Sperm volume regulation in response to such osmotic challenges is important to maintain a stable cell size for the normal shape and function of the sperm tail. Alongside ion channels for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 89 publications
1
42
1
Order By: Relevance
“…13 The role of AQP7 in tumours is unclear, however, in the present study, weak AQP7 staining was found in the plasma membranes of benign The reason for this distribution of AQP7 is largely unknown. Several studies have reported that AQP7 may act as the sole glycerol facilitator and may be associated with energy production in heart tissue of mice and skeletal muscles, 2,3,6 and may be involved in sperm motility 14 and glycerol reabsorption in the kidney. 13 In the present study, semiquantitative analysis by Western blotting indicated that the AQP7 protein expression level in malignant and borderline tumours was significantly higher than that in benign tumours and normal ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…13 The role of AQP7 in tumours is unclear, however, in the present study, weak AQP7 staining was found in the plasma membranes of benign The reason for this distribution of AQP7 is largely unknown. Several studies have reported that AQP7 may act as the sole glycerol facilitator and may be associated with energy production in heart tissue of mice and skeletal muscles, 2,3,6 and may be involved in sperm motility 14 and glycerol reabsorption in the kidney. 13 In the present study, semiquantitative analysis by Western blotting indicated that the AQP7 protein expression level in malignant and borderline tumours was significantly higher than that in benign tumours and normal ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…5B). An examination of the stage at which spermatids are retained (see above), the morphology of the retained spermatids by electron microscopy, immunohistochemistry of appropriate markers of the spermiation machinery ( Table 1) and markers of spermatid cytoplasm such as aquaporin 11, 71 will provide insight into the mechanism of spermiation failure.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…system is still controversial. Current findings seem to indicate a major role of AQP7 in glycerol metabolism and a possible role of AQP8 in water movement for sperm volume regulation [Yeung 2010]. Recently, AQP11 was identified in the residual cytoplasm of rat elongating spermatids and in the distal region of the sperm flagellum, suggesting a function in recycling the excess of cytoplasmic components required to make the sperm slim enough to be able to swim fast and reach the oocyte.…”
Section: Introductionmentioning
confidence: 99%